064. Overview of Bacterial Patterns and Antibiotic Resistance on Cholangitis Patients at Hasan Sadikin General Hospital from January to December 2023 - Evan, Cecilia; Rudiman, Reno (JBN (Jurnal Bedah Nasional), 2024)
Background : Cholangitis is a serious infection of the bile ducts that requires prompt treatment, often with antibiotic therapy. Although antibiotic use, especially ceftriaxone and metronidazole, is vital in treatment, antibiotic resistance remains a significant challenge. Unfortunately, data on bacterial resistance patterns in cholangitis patients treated at Doctor Hasan Sadikin Hospital in Bandung is still limited. This study aims to describe the bacterial patterns and antibiotic resistance in cholangitis patients at Doctor Hasan Sadikin General Hospital. Another objective is to assess the effectiveness of ceftriaxone and metronidazole therapy in patients with moderate to severe cholangitis. Methods : This research employed a retrospective descriptive design by collecting data from the medical records of acute cholangitis patients treated at Doctor Hasan Sadikin General Hospital from January to December 2023. A total of 126 patient samples meeting the inclusion criteria were analyzed through blood cultures, and sensitivity tests were conducted against various antibiotics. Data were analyzed using SPSS software. Results : The results showed that Escherichia coli (26.3%) was the most commonly found bacterium, followed by Staphylococcus haemolyticus and Klebsiella pneumoniae (each at 13.2%). The highest resistance was observed against ampicillin (78.9%), while the most effective antibiotic was tigecycline (92.1% sensitivity). Conclusion: In conclusion, ceftriaxone and metronidazole as empiric therapy remains effective for most cholangitis patients, although resistance to certain antibiotics like ampicillin warrants attention. This study highlights the importance of regular monitoring of antibiotic resistance patterns to ensure proper treatment and reduce morbidity and mortality rates among cholangitis patients.